Speech Acts and Sasak Language Variations in ‘Pe Buling’ Family Clan Communication in Senyiur Village Based on Islamic Values - Ahmad Turmuzi (ISLAMIKA, 2026)
This study is motivated by the limited empirical research that holistically examines speech acts, Sasak language variation, and the integration of Islamic moral values within family-based communication. It aims to analyze the forms and functions of speech acts, patterns of Sasak language variation, sociocultural and situational influences on language choice, and the manifestation of Islamic values in everyday familial discourse within the Pe Buling family clan. The study employed a qualitative case study design involving 20 purposively selected participants in Senyiur Village, representing different kinship roles and generations within a Sasak-speaking family clan. Data were collected through participant observation, semi-structured interviews, and audio recordings of natural interactions, and were analyzed thematically using an interactive qualitative model grounded in pragmatics and sociolinguistics. The findings reveal that communicative interactions are systematically structured through representative, declarative, directive, expressive, and commissive speech acts. Representative and declarative acts play a central role in establishing shared understanding and legitimizing collective decisions, while directive acts are predominantly realized in softened and indirect forms, particularly in intergenerational communication. Sasak language variation, especially the alternation between honorific basa alus and everyday basa jama-jama forms, reflects speakers’ pragmatic competence in managing social hierarchy and situational demands. The study concludes that speech acts and language variation function as moral instruments through which Islamic values, including respect, humility, sincerity, and moral responsibility, are continuously enacted and transmitted in family communication. This study contributes to pragmatics and sociolinguistics by integrating Islamic communication ethics into the analysis of speech acts and local language variation, while also recommending future comparative and multi-site research on family-based moral communication in multilingual communities.